H0LiCOW – V. New COSMOGRAIL time delays of HE 0435−1223: H0 to 3.8 per cent precision from strong lensing in a flat ΛCDM model. Issue 4 (22nd November 2016) - Bonvin, V.; Courbin, F.; Suyu, S. H.; Marshall, P. J.; Rusu, C. E.; Sluse, D.; Tewes, M.; Wong, K. C.; Collett, T.; Fassnacht, C. D.; Treu, T.; Auger, M. W.; et al.
Abstract: We present a new measurement of the Hubble Constant H 0 and other cosmological parameters based on the joint analysis of three multiply imaged quasar systems with measured gravitational time delays. First, we measure the time delay of HE 0435−1223 from 13-yr light curves obtained as part of the COSMOGRAIL project. Companion papers detail the modelling of the main deflectors and line-of-sight effects, and how these data are combined to determine the time-delay distance of HE 0435−1223. Crucially, the measurements are carried out blindly with respect to cosmological parameters in order to avoid confirmation bias. We then combine the time-delay distance of HE 0435−1223 with previous measurements from systems B1608+656 and RXJ1131−1231 to create a Time Delay Strong Lensing probe (TDSL). In flat Λ cold dark matter (ΛCDM) with free matter and energy density, we find H 0 $=71.9^{+2.4}_{-3.0}\ {\rm km\, s^{-1}\, Mpc^{-1}}$ and $Ω _{Λ }=0.62^{+0.24}_{-0.35}$ . This measurement is completely independent of, and in agreement with, the local distance ladder measurements of H 0 . We explore more general cosmological models combining TDSL with other probes, illustrating its power to break degeneracies inherent to other methods. The joint constraints from TDSL and Planck are H 0 = $69.2_{-2.2}^{+1.4}\ {\rm km\, s^{-1}\, Mpc^{-1}}$, $Ω _{Λ }=0.70_{-0.01}^{+0.01}$ and $Ω _{\rm k}=0.003_{-0.006}^{+0.004}$ in open ΛCDM and H 0 $=79.0_{-4.2}^{+4.4}\ {\rm km\, s^{-1}\, Mpc^{-1}}$, $Ω _{\rm de}=0.77_{-0.03}^{+0.02}$ and $w=-1.38_{-0.16}^{+0.14}$ in flat w CDM. In combination with Planck and baryon acoustic oscillation data, when relaxing the constraints on the numbers of relativistic species we find Neff = $3.34_{-0.21}^{+0.21}$ in Neff ΛCDM and when relaxing the total mass of neutrinos we find Σmν ≤ 0.182 eV in mν ΛCDM. Finally, in an open w CDM in combination with Planck and cosmic microwave background lensing, we find H 0 $=77.9_{-4.2}^{+5.0}\ {\rm km\, s^{-1}\, Mpc^{-1}}$, $Ω _{\rm de}=0.77_{-0.03}^{+0.03}$, $Ω _{\rm k}=-0.003_{-0.004}^{+0.004}$ and $w=-1.37_{-0.23}^{+0.18}$ .